Implementation of Presidential Instruction Number 3 of 2014 by the Regional Government in Optimizing the Collection of Zakat, Infaq, and Sedekah for ASN in Bukittinggi City - Satria, Boedi; Rizal, Rizal; Paizin, Muhsin Nor (Muttaqien, 2026)
The management of zakat, infaq, and alms (ZIS) by the State Civil Apparatus (ASN) plays an important role in regional socio-economic development, but its implementation often faces structural and administrative challenges. This study analyzes the implementation of Presidential Instruction Number 3 of 2014 by the Bukittinggi City Government in the collection of ZIS for ASN. The method used is qualitative with a case study at BAZNAS Bukittinggi City, involving BAZNAS administrators, regional officials, and ASN as informants. Data were obtained through interviews, observations, and document analysis, such as ZIS reports and regional regulations. The analysis was carried out using the Miles & Huberman model, through data reduction, presentation, and drawing conclusions, with data validity strengthened by triangulation. The results show that policy implementation has been carried out through payroll mechanisms and regulatory support, but its effectiveness is limited by uneven socialization, ASN resistance to automatic deductions, differences in treatment between OPDs regarding TPP deductions, and limited BAZNAS human resources. There is a picture between the potential for ASN ZIS reaching ± Rp. 12 billion per year and the realization of only around Rp. 2.55 billion. Therefore, policy implementation remains suboptimal and requires greater institutional capacity, regulatory harmonization, and civil servant zakat literacy.